The Governance Structures of Chinese Firms Innovation, Competitiveness, and Growth in a Dual Economy - Liao, Chun (Innovation, Technology, and Knowledge Management, 2009)
China's extraordinary economic growth is inspiring research from a wide spectrum of fields to explain the phenomenon: What are the primary drivers of China's economic growth? Can it be sustained? Can the Chinese business model be emulated by other countries? What long-term effects will China's economic growth have on the global economy? In this volume, Chun Liao explores these issues in the context of firms' governance structures, arguing that China's dual business system of state-owned enterprises and private enterprises is uniquely suited to the challenges of economic development in the twenty-first century. On the one hand, China's state-owned enterprises are characterized by state coordination, bank financing, insulation from the stock market fluctuations, and incremental productivity-enhancing innovations, which are similar to the firms in the business systems of coordinated market economies (like Germany and Japan). On the other hand, China's private enterprises are characterized by private (often family) ownership, hard budget constraints, profit maximization, and more risky radical innovation, which are similar to the firms in the business systems of liberal market economies (like the US and the UK). Based on the state controlling shareholding in the state sector, the boundary between the state sector business system and private sector business system is clear. This dual type system is contrasted with those in liberal market economies and those in coordinated market economies, where only one type system dominates. Drawing from empirical data and industry analysis over the past 15 years, Liao provides unparalleled access to the dynamics of the Chinese economy, including ownership structure, management design, labor-management relations, business infrastructure, capitalization (including role of banks and financial institutions, private investment, and FDI) in both the public and private sectors. In the process, she analyzes both opportunities and challenges that result from China's dual business system, particularly in regard to innovation, core competitiveness, and sustainable growth in both state strategic technology-based industries and private high technology industries . The result is an approach that sheds new light on China's economic performance and its rise as a player on the international stage.